Moral Neuroenhancement - Douglas, Thomas (2017)
In this chapter, we introduce the notion of “moral neuroenhancement,” offering a novel definition as well as spelling out three conditions under which we expect that such neuroenhancement would be most likely to be permissible (or even desirable). Furthermore, we draw a distinction between first-order moral capacities, which we suggest are less promising targets for neurointervention, and second-order moral capacities, which we suggest are more promising. We conclude by discussing concerns that moral neuroenhancement might restrict freedom or otherwise “misfire,” and argue that these concerns are not as damning as they may seem at first